Traditional Chinese Medicine Syndromes for Essential Hypertension: A Literature Analysis of 13, 272 Patients. (10th February 2014) - Wang, Jie; Xiong, Xingjiang; Liu, Wei
Abstract : Background . To simplify traditional Chinese medicine syndrome differentiation and allow researchers to master syndrome differentiation for hypertension, this paper retrospectively studied the literature and analyzed syndrome elements corresponding to hypertension syndromes. Methods . Six databases including PubMed, EMBASE, Chinese Bio-Medical Literature Database, Chinese National Knowledge Infrastructure, Chinese Scientific Journal Database, and Wan-fang Data were searched from 1/January/2003 to 30/October/2013. We included all clinical literature testing hypertension syndromes and retrospectively studied the hypertension literature published from 2003 to 2013. Descriptive statistics calculated frequencies and percentages. Results . 13, 272 patients with essential hypertension were included. Clinical features of hypertension could be attributed to 11 kinds of syndrome factors. Among them, seven syndrome factors were excess, while four syndrome factors were deficient. Syndrome targets were mainly in the liver and related to the kidney and spleen. There were 33 combination syndromes. Frequency of single-factor syndromes was 31.77% and frequency of two-factor syndromes was 62.26%. Conclusions . Excess syndrome factors of hypertension patients include yang hyperactivity, blood stasis, phlegm turbidity, internal dampness, and internal fire. Deficient syndrome factors of hypertension patients are yin deficiency and yang deficiency. Yin deficiency with yang hyperactivity, phlegm-dampness retention, and deficiency of both yin and yang were the three most common syndromes in clinical combination.